Save it for Sunday - Johnstone, William W.; Johnstone, J. A. (Johnstone, William W. Taylor Callahan, circuit rider (Series), 2023)
A repentant preacher, circuit rider Taylor Callahan, taking over as sheriff in Peaceful Valley, finds his trigger-happy past coming back with a vengeance, forcing him to break his "no more violence" vow as he straps on his Colt .45 once again